Emergencja duszy. Andreasa Nordlandera odczytanie potencjalizmu św. Augustyna i kwestia stworzenia duszy ludzkiej w ewoluującym wszechświecie - Tomasz Maziarka (Studia Philosophiae Christianae)
This article takes up the question of the creation of the human soul in the context of evolution, using St. Augustine’s interpretive framework. The Bishop of Hippo advocates the gradual emergence of the world and its wealth of things from the potentialities contained in materia informis and rationes seminales created ex nihilo. Such a vision of the development of nature fits very well with the evolutionary picture of the world drawn by the natural sciences, which reveals the emergence of new phenomena as a result of the formation of increasingly complex structures. The creation of the human soul calls for detailed consideration. Augustine’s classical solution says that only the human body could have been created by natural development, while the soul was brought into existence by a separate act and then “poured” into the body. From a naturalistic point of view, this solution faces some difficulties. However, it turns out that they can be avoided with the heuristic tools provided by Augustine , and that it is possible to conceive of a scenario in which the whole human being with soul and body comes into existence through evolution. Although this solution involves going beyond the framework of St. Augustine’s anthropology, it is entirely consistent with his idea of potentialism. This more radical potentialism, which is consistent with the natural sciences, defuses the tensions within Bishop’s anthropology and at the same time makes a valuable contribution to the dialogue between science and religion.